Role of Fintech Adoption In User Quality of Life: A UTAUT-Based Study In Surabaya, Indonesia - Adi Kurniawan Yusup; Deanna Rhea Chang (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study examines how UTAUT constructs influence FinTech adoption and how this adoption affects Quality of Life (QoL) in Surabaya, Indonesia. The research is driven by the rising use of digital financial services in Indonesia and the need to understand whether this behavior supports or reduces user well-being. Methodology: This research employs a quantitative approach using purposive sampling. Data were collected from 123 FinTech users and analyzed using PLS-SEM. Results: All UTAUT constructs positively influence FinTech adoption, except Effort Expectancy, which is insignificant (p = 0.301). FinTech adoption positively influence user’s QoL (p = 0.000) and mediates Performance Expectancy, Social Influence, and Facilitating Conditions on QoL, but not Effort Expectancy (p = 0.329). Findings: Facilitating Conditions are the strongest predictor of adoption. The weak role of Effort Expectancy presents a different pattern compared to some earlier studies. Novelty:  The study provides evidence on how adoption factors relate to well-being in an Indonesian metropolitan city. Originality: The research reveals a distinct empirical patterns, particularly the dominant role of Facilitating Conditions and the weak influence of Effort Expectancy. Conclusion: FinTech adoption supports better QoL in Surabaya, highlighting the importance of improved infrastructure and user support. Type of Paper: This paper is an empirical research paper.